Sustainable Development of Energy, Water and Environment Systems (SDEWES 2021) - Sahin, Oz; Bertone, Edoardo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains collections of selected articles presented at the SDEWES2021 conference and subsequently published in a special issue of Sustainability. The book provides state-of-the-art research, overviewing practices in sustainable development, energy, water and environment systems, as well as their uses and applications. Focus is given to waste management; higher biomass production; biorefineries; bio-digital interface and microbial fuel cells; energy and cost reduction in the building sector; and the economic impact of sustainability.